Survei Kemampuan Guru Menerapkan Pendekatan Saintifik dalam Pembelajaran Senam Ketangkasan di SMA Negeri 5 Buru - Batauga, Elvi; Fenanlampir, Albertus; Souisa, Mieke (MANGGUREBE: Journal Physical Education, Health and Recreation, 2025)
The application of the scientific approach in Physical Education, Sports, and Health (PJOK) plays a crucial role in enhancing the quality of the teaching and learning process. This study aims to examine the extent to which PJOK teachers implement the scientific approach in classroom instruction, particularly in the subject of gymnastics skills. This is a descriptive study using a qualitative approach. Data were collected through observation, interviews, documentation, and triangulation, and analyzed using qualitative methods. The research subjects were PJOK teachers at SMA Negeri 5 Buru, located in Sawa Village, Lilialy District, selected through purposive and snowball sampling techniques, based on their roles and competencies. The findings indicate that teachers generally apply the scientific approach adequately in the learning process. However, its implementation is not yet optimal, mainly due to the lack of active student participation during classroom activities. These results suggest that the success of the scientific approach depends not only on the teacher’s competence but also on the students’ engagement in the learning process.